High-sensitivity multi-channel DPSK system with real-time phase lock controller for free-space optical communication - Gao, Duorui; Li, Tianlun; Xie, Zhuang; Meng, Jiacheng; Jia, Shuaiwei; Bai, Zhaofeng; Wang, Wei; Xie, Xiaoping (Frontiers in Physics, 2022)
To conquer the power jitters aroused by the atmosphere turbulence for satellite-ground communication, a type of DPSK free-space communication system assisted by self-designed real-time phase lock controller has been established which can effectively compensate the power swings of communication links to achieve high-sensitivity. The wavelength division multiplexing technique has been applied for the four-channel DPSK system to provide greater link capacity. With the data rate of a single channel as 2.5Gbps and unencoded BER as 10-3, the receiving sensitivity has been obtained as -53.58 dBm (13.69 photons/bit), -53.59 dBm (13.66 photons/bit), -53.61 dBm (13.59 photons/bit), -53.63 dBm (13.53 photons/bit) for each independent channel, respectively. The gap between our sensitivity result and theoretical limit has been narrowed about to -3.5dB. Simultaneously, the DPSK receiver with our self-designed phase lock controller has been well-confirmed to have stabilized adaptability for received optical power fluctuation ranging from 0-40dB. Additionally, the impact of four-wave mixing effect on multi-channel system performance has been investigated in detail. Our experiment results imply a novel solution for superior performance of free-space communication links.